(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The present study examines pressing issues in urban landscape architecture, particularly the reduction of green spaces in modern cities, the overutilization of recreational parks for amusement rides, and the gradual disappearance of traditional boulevards and promenades. These trends contribute to the degradation of the urban environment and limit public access to natural spaces. The article proposes sustainable urban planning solutions aimed at reversing these effects by promoting the integration of green zones throughout urban territories. Special attention is given to the development of continuous green corridors by increasing the planting of ornamental trees along pedestrian walkways, canal banks, and irrigation ditches. This approach envisions transforming each city district into an interconnected segment of a broader recreational landscape. The paper argues that such measures will contribute to the creation of an ecologically clean and inclusive urban environment, enhancing the quality of life for city residents. The proposed strategies emphasize the importance of preserving and revitalizing natural elements within the cityscape through environmentally conscious and inclusive design practices.